Complications after simultaneous prepectoral breast reconstruction using polyurethane-coated implants in patients with breast cancer - M. Yu. Vlasova; A. D. Zikiryakhodzhaev; I. V. Reshetov; F. N. Usov; E. K. Saribekyan; I. M. Shirokikh; A. N. Gerasimov; Sh. G. Khakimova; M. V. Starkova; N. V. Ablitsova; А. V. Tregubova; T. S. Berestok (Опухоли женской репродуктивной системы)
Background. The development and improvement of reconstructive breast surgery provides medical, psychological and social rehabilitation of cancer patients, allowing them to achieve the best cosmetic and functional results. The trend towards the return of prepectoral reconstruction is associated not only with the improvement of mastectomy techniques, but also with implant coating and the emergence of highly cohesive silicone gel filling of implants. The use of polyurethane-coated endoprostheses in prepectoral reconstruction provides more reliable fixation to the surrounding tissues and allows reconstruction of the mammary glands without additional covering of the endoprosthesis.Objective: to improve the results of surgical treatment when performing a one-stage reconstruction by pre-rectal placement of polyurethanecoated implants in breast cancer. Materials and methods. In the period from April 2017 to September 2020 at the Department of Oncology and Reconstructive Plastic Surgery of the Breast and Skin of P.A. Herzen Moscow Oncology Research Institute performed 340 prepectoral breast reconstructions (direct-toimplant) using polyurethane-coated implants in breast cancer patients. A group of patients was analyzed (n = 208).Results. We noted the following complications: prolonged seroma (more than 30 days) in 39 (18.6 %) patients, red breast syndrome in 31 (14.8 %) patients, capsular contracture III–IV degree by J.L. Baker in 43 (20.57 %) patients, protrusion/extrusion of the endoprosthesis in 23 (11 %) patients, suture divergence in 8 (3.8 %) patients, necrosis in 8 (3.8 %) patients, infectious complications in 14 (6.7 %) patients, ripping in 10 (4.8 %) patients. Also, 2 (0.95 %) patients had a violation of the integrity of the endoprosthesis, and 2 (0.95 %) patients had rotation of the endoprosthesis. Conclusions. Prepectoral breast reconstruction can be used as an alternative to subpectoral reconstruction in primary operable forms of breast cancer with sufficient thickness of integumentary tissues.